Optimizing commensality of radio continuum and spectral line observations in the era of the SKA - Maddox, N; Jarvis, M; Oosterloo, T (Oxford University Press, 2016)
The substantial decrease in star formation density from z = 1 to the present day is curious given the relatively constant neutral gas density over the same epoch. Future radio astronomy facilities, including the Square Kilometre Array (SKA) and pathfinder telescopes, will provide pioneering measures of both the gas content of galaxies and star formation activity over cosmological time-scales. Here we investigate the commensalities between neutral atomic gas (H I) and radio continuum observations, as well as the complementarity of the data products. We start with the proposed H I and continuum surveys to be undertaken with the SKA precursor telescope MeerKAT, and building on this, explore optimal combinations of survey area coverage and depth of proposed H I and continuum surveys to be undertaken with the SKA1-MID instrument. Intelligent adjustment of these observational parameters results in a tiered strategy that minimizes observation time while maximizing the value of the data set, both for H I and continuum science goals. We also find great complementarity between the H I and continuum data sets, with the spectral line H I data providing redshift measurements for gas-rich, star-forming galaxies with stellar masses M * ~ 10 9 M ⊙ to z ~ 0.3, a factor of 3 lower in stellar mass than would be feasible to reach with large optical spectroscopic campaigns.